Question

If *g* (*x*) = −2*x* + 7, find the new function defined by *h* (*x*) = *g* (2*x* ^{2} + 1).

Find answers to questions asked by students like you.

Q: How to find f-1(x) of f(x)=x2-18x. Can you please give steps as well.

A: The given function is f(x) = x2–18x.Replace f(x) by y as y = x2–18x.Interchange the variables and so...

Q: how to simplify tan(arcsin(x))?

A: Start with:

Q: Consider the following. x = sin(t), y = csc(t), 0 < t < π/2 (a) Eliminate the paramete...

A: x(t) = sin(t)y(t) =csc(t)

Q: TIMN the MISSing part oi this Equation. Note: your answer should be in the form of one or more fract...

A: 1 micro gram= 10^-6 gram =1/10^6 gram

Q: If a ball is thrown straight up into the air with an initial velocity of 70 ft/s, it's height in fee...

A: The height of the ball thrown straight up into the air after t seconds is given by t=70t-16t2.The av...

Q: Find the average value fave of the function f on the given interval. f(t) = esin(t) cos(t), [0, π...

A: Given that

Q: Find the derivative of y with respect to x. 58)y tan (In 2x)

A: Firstly, we use the result that derivative of inverse of tan of x is 1/1+x^2

Q: Struggling with guestion 1.

A: At the outset, I want to state that in the hand written question the amount of interest figure is no...

Q: Can I get help with this question step by step?

A: Given values of f(x), L, c and Ɛ>0 are